Analytical Study on the Rational Challenges Project Engineering Managers Encounter Prior to Achieving Sustainability in the UK Construction Industries - Uzoigwe, Stella Awele Asoya; Atoofi, Maryam; Lewis, Hollie; Onyedikachukwu, Ndekwu, Benneth (Journal of Engineering Research and Reports, 2023)
Aim: The essential purpose of the current research was to identify the challenges faced by project engineering managers in the UK construction industry while seeking to achieve sustainability. Study Design: The current study was built upon six important subjects in order to accomplish this goal. In the current study, the researcher opted to do both qualitative and quantitative analysis. The quantitative analysis comprised frequency analysis, correlation analysis, and regression analysis and was based on data collected through questionnaires. Place and Duration of Study: This study was carried out in Bristol United Kingdom for an investigative period of six (6) Months including the research question distribution and collection time as well as the interview and interaction sections with the Construction Project Engineering Managers. Methodology: In light of the nature of the current research, the researcher selected the mixed research design. Mixed research design is the method used in collecting and analyzing data by using both qualitative and quantitative research methodologies. Results: The results of the present study showed that effective health and safety management systems are necessary for sustainable construction. However, the UK construction industry lacks these systems. The study also identified lack of education and training as a hindrance. The proper understanding of the project and its processes can only be attained through training and education, and managers have to deal with the problem of being unable to successfully complete sustainable building owing to lack of such resources. However, with the right on-the-job training and efficient monthly meetings that include training and education sessions, this can be improved. Conclusion: The study resolved that policies should be put in place to guarantee that advancement in the building sector follows economic integration. It has been revealed from the findings that construction is heavily dependent on conventional methods in most rising economies, including the UK, which makes the adoption of novel techniques more challenging and stressful. An important barrier to attaining sustainable construction is clients' and other stakeholders' lack of support for innovative construction techniques. The findings further revealed that the implementation of eco-friendly building practices by the construction sector has the tendency to reduce an asset's overall environmental impact and promote sustainable economic growth.